A educação ambiental e a arte-educação: interlocuções em uma escola da rede pública do município de Santa Helena-PR - Demenighi, Solange (2025)
Environmental Education (EE) is not a recent topic, but in schools, as they are spaces for coexistence, learning and developing critical thinking, its importance can be highlighted in relation to caring for the environment. This study, “Environmental Education and Art Education: Interlocutions in a Public School in the Municipality of Santa Helena-Pr”, aimed to analyze active and interdisciplinary learning practices carried out with students in the 1st Year of Primary School, through Art, using the Triangular Approach (TA), to raise students' awareness of environmental issues. The aim was to answer the following question: How does Critical Environmental Education (CAT) linked to Art, using TA, contribute to raising awareness of environmental issues among elementary school students? The methodology is qualitative quantitative, with the principles of participant research, consisting of 10 interventions, the data collection instruments were the students' Drawings A and B. These were analyzed using the Draw-an-Ecosystem Test (DET), Student's T-Test and Content Analysis from a descriptive perspective. The results in Drawings A and B of the DET markers presented are in relation to representations of human figures, biotic and abiotic elements and human constructions. After educational interventions on environmental issues, there was an increase in representations of human figures (42.4% - 48.5%), fauna (54.5% - 66.7%), flora (93.9%), abiotic elements (81.8% - 94%) and human constructions (72.7% - 87.9%), showing greater environmental awareness nd complexity in representations. The quantitative data from the student’s t-test reveals significant differences in some markers between Drawings A and B. With an increase in the presence of abiotic elements (mean A=0.848; B=1.394) and human constructions (mean A=1.242; B=2.485), with greater dispersion in Drawing B. The markers of human presence (mean A=0.636; B=0.848) and biotic elements (mean A=1.879; B=1.848) showed no significant differences. The qualitative results of the T-Test indicate significant differences between Drawings A and B in relation to abiotic elements and human constructions, and also enabled three categories to emerge for the Content Analysis: Representation of the Biotic and Abiotic Environment, Representations of Humans and Human Constructions, and Interactions and Criticality. The educational interventions in EE, mediated by Art Education and TA, were fundamental in mobilizing knowledge and broadening the students' environmental sensitivity.